2001
DOI: 10.1111/j.1365-313x.2001.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

The MuDR transposon terminal inverted repeat contains a complex plant promoter directing distinct somatic and germinal programs

Abstract: Summary The Mu transposons of maize are under stringent developmental control. Elements excise at high frequencies in terminally dividing somatic cells, but not in meristems. Mu elements in germinal cells amplify, without excision, and insert throughout the genome. All activities require MuDR, which encodes two genes, mudrA and mudrB, whose near‐identical promoters are located in the transposon terminal inverted repeats (TIR). We have fused the 216 bp TIR of the mudrB gene to GUS and luciferase reporters. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 62 publications
(105 reference statements)
2
11
0
Order By: Relevance
“…Previous work established that a maize Ubi1 promoter is highly active in most maize tissues, including roots, developing anthers, and pollen (Raizada et al, 2001a). We confirmed that Ubi1 transcripts also are abundant in aleurone cells through 30 days after pollination ( Figure 5B), when mitotic proliferation has finished and when most Mu1 excisions have occurred (Levy and Walbot, 1990;Raizada and Walbot, 2000).…”
Section: Generation and Characterization Of Transgenic Plants Expresssupporting
confidence: 83%
“…Previous work established that a maize Ubi1 promoter is highly active in most maize tissues, including roots, developing anthers, and pollen (Raizada et al, 2001a). We confirmed that Ubi1 transcripts also are abundant in aleurone cells through 30 days after pollination ( Figure 5B), when mitotic proliferation has finished and when most Mu1 excisions have occurred (Levy and Walbot, 1990;Raizada and Walbot, 2000).…”
Section: Generation and Characterization Of Transgenic Plants Expresssupporting
confidence: 83%
“…Thus, it would appear that MURB is required for integration of Mutator elements, but not their excision. In situ analysis suggests that both mudrA and mudrB are expressed at highest levels in actively dividing cells and in pollen, consistent with the observation that the MuDR TIRs contain plant cell-cycle enhancer motifs and functionally defined pollen enhancers (16,22,23). Antibody analysis of MURB expression has shown that MURB protein is present at highest levels in actively dividing cells, particularly those in floral meristems, an observation that is consistent with in situ analysis of RNA expression (16,23).…”
Section: Autonomous Mudr Elementsmentioning
confidence: 56%
“…Since the transcription start site for 153 of 235 transcripts that initiate within a MULE sequence is located <500 bp from the element terminus, the promoter is likely located within the TIR. In fact, the TIRs of the maize MuDR element harbor promoters for mudrA and mudrB (Raizada et al 2001), and while the TIR sequences of rice and maize MULEs are divergent, the majority of rice MULE TIRs contain putative TATA boxes and other promoter elements. In addition, transposition of MULEs with transduplicates may bring them into proximity to other cis-regulatory sequences.…”
Section: Genome Research 1293mentioning
confidence: 99%